2009
DOI: 10.1242/dev.032177
|View full text |Cite
|
Sign up to set email alerts
|

DORNRÖSCHENis a direct target of the auxin response factor MONOPTEROS in theArabidopsisembryo

Abstract: 1, †DORNRÖSCHEN (DRN), which encodes a member of the AP2-type transcription factor family, contributes to auxin transport and perception in the Arabidopsis embryo. Live imaging performed with transcriptional or translational GFP fusions shows DRN to be activated in the apical cell after the first zygotic division, to act cell-autonomously and to be expressed in single cells extending laterally from the apical shoot stem-cell zone at the position of incipient leaf primordia. Here, we show that the Auxin respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
168
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 51 publications
(78 reference statements)
4
168
1
2
Order By: Relevance
“…3H). Similarly, the weak loss-of-function mp S319 mutant (22) exhibited zones of ectopic pericycle cell division, although they were less pronounced (Fig. 3I).…”
Section: Bdl-mp-dependent Auxin Response Module Acts In Lateral Rootmentioning
confidence: 90%
“…3H). Similarly, the weak loss-of-function mp S319 mutant (22) exhibited zones of ectopic pericycle cell division, although they were less pronounced (Fig. 3I).…”
Section: Bdl-mp-dependent Auxin Response Module Acts In Lateral Rootmentioning
confidence: 90%
“…Previous studies have shown that the auxininducible transcription factor ARF5/MONOPTEROS (MP) binds the ESR1/DRN promoter and activates its expression during embryonic development (Cole et al, 2009). The ESR1/DRN promoter possesses two canonical auxin-responsive elements where ARF5/MP binds in vivo, and mutations in these sequences alter auxin-induced expression of ESR1/DRN in developing embryos (Cole et al, 2009).…”
Section: Activation Of Esr1 Expression By Auxin and Cytokininmentioning
confidence: 99%
“…Previous studies have shown that the auxininducible transcription factor ARF5/MONOPTEROS (MP) binds the ESR1/DRN promoter and activates its expression during embryonic development (Cole et al, 2009). The ESR1/DRN promoter possesses two canonical auxin-responsive elements where ARF5/MP binds in vivo, and mutations in these sequences alter auxin-induced expression of ESR1/DRN in developing embryos (Cole et al, 2009). Interestingly, the expression of ARF5/MP is strongly upregulated in explants cultured on CIM and SIM (Che et al, 2006), raising the possibility that ARF5/MP might participate in auxin-induced ESR1 expression in cultured explants.…”
Section: Activation Of Esr1 Expression By Auxin and Cytokininmentioning
confidence: 99%
“…Recently, it was shown that DORNRÖ SCHEN (DRN) is such a direct target (Chandler et al 2007;Cole et al 2009). DRN encodes an AP2-type transcription factor and acts redundantly with its paralog DRN-like (DRNL) in cotyledon development.…”
Section: Role Of Auxin In Shoot Meristem Formation and Cotyledon Formmentioning
confidence: 99%